Role of lumbar spine signal intensity measurement by MRI in the diagnosis of osteoporosis in post-menopausal women - Maha M. Saad; Ahmed Tohamy Ahmed; Khaled E. Mohamed; Mohamed R. Habba (The Egyptian Journal of Radiology and Nuclear Medicine, 2019)
Abstract Background Osteoporosis is a worldwide health problem and a common cause of bone fractures; the most common type of osteoporosis is post-menopausal type. MRI has a role in the diagnosis of osteoporosis and can be used as a screening tool, so the purpose of our study was to define a quantitative MRI-based score (M-score) for the detection of lumbar spine osteoporosis and to evaluate the correlation between lumbar spine signal intensity measured by MRI and BMD (bone mineral density) in post-menopausal women. Our case-control study involved 100 cases (50 old post-menopausal females as a case group and 50 healthy females as a control group of matched age). Both groups were subjected to history taking, dual-energy X-ray absorptiometry (DEXA), and conventional lumbar MRI. DEXA was performed for the lumbar spine and all scores (T-score, Z-score, BMD) were calculated. Lumbar MRI was performed (sagittal T1WI and T2WI) from L1–L4 levels. SNRL1–L4 and M-score were calculated from T1W images. Results All DEXA scores were significantly lower in post-menopausal females compared to the control group (P < 0.0001). Meanwhile, SNRL1–L4 and M-score were significantly higher among cases than controls (P < 0.0001). The diagnostic threshold of SNRL1–L4 and M-score for distinguishing osteoporotic from non-osteoporotic females was 104.5 for SNRL1–L4 with a sensitivity of 94%, specificity 60%, positive predictive values (PPV) 31%, and negative predictive values (NPV) 98%, and 3.5 for M-score with a sensitivity of 93.3%, specificity 83.5%, PPV 50%, and NPV 98.6%. SNRL1–L4 was negatively correlated with M-score (r = − 0.74, P < 0.0001), T-score (r = − 0.42, P < 0.0001), Z-score (r = − 0.32, P < 0.0001), and BMD (r = − 0.31, P < 0.0001). M-score was negatively correlated with T-score (r = − 0.48, P < 0.0001), Z-score (r = − 0.36, P < 0.0001), and BMD (r = − 0.37, P < 0.0001). M-score moderately agreed with T-score (κ = 0.5, P < 0.0001). Conclusion The MRI-based score (M-score) of the lumbar spine is an accurate quantitative method for distinguishing osteoporotic from non-osteoporotic females. M-score and SNRL1–L4 are significantly correlated with osteoporotic indices (T-score and BMD).